The Association Between Seeing People Walk and Neighborhood Social Cohesion - Murillo, Rosenda (Health Behav Policy Rev, 2019)
OBJECTIVES: To examine the association between frequency of seeing people walk within sight of home and neighborhood social cohesion among adults, and whether this association varies by race/ethnicity. METHODS: We used cross-sectional 2015 National Health Interview Survey data on Latino, non-Latino White, non-Latino Black, and non-Latino Asian adults (N = 33,099). Multinomial logistic regression models were used to estimate the associations. RESULTS: Seeing people walk every day and every 2-3 days were significantly more likely to report medium levels of neighborhood social cohesion, relative to low. The association between seeing people walk and neighborhood social cohesion varied by race/ethnicity. CONCLUSIONS: Higher frequency of seeing others walk may contribute to higher levels of neighborhood social cohesion.